The brain-body circuit mediates acute stress-induced anti-inflammatory reflex in bacterial cystitis by suppressing ILC2 activation - Yaxiao Liu; Jinhua Wang; Junyang Lin; Dingqi Sun; Kejia Zhu; Tongxiang Diao; Qiang Fu; Qingyu Ren (JCI Insight, 2025)
Urinary tract infections (UTIs) are one of the most commonly encountered infections in clinical practice, in which psychological stress is a critical pathological contributor to modulate immune function. However, mechanistic pathways linking stress networks in the brain to bladder infection remain poorly understood. In this study, we discovered that acute stress treatment suppressed bladder inflammation in mice with UTIs, and a significant number of neurons showing overlap between inflammation-associated markers and retrograde labeling were observed in the paraventricular nucleus (PVN) brain region of these mice. Activation of PVN alleviated UPEC-induced bladder inflammatory response. Moreover, blocked hypothalamic-pituitary-adrenal (HPA) axis reversed the anti-inflammatory reflex mediated by acute stress, suggesting that the potential of glucocorticoids levels through the brain-body circuits to ameliorate UTIs. Single cell-RNAseq of bladder immune cells revealed that type 2 innate lymphoid cells (ILC2) expressed abundant levels of glucocorticoid receptor (GR). The activation of PVN effectively inhibited the expression of the proinflammatory cytokine Csf2 by ILC2 through direct regulation of cell-intrinsic glucocorticoids signaling. Ultimately, our study has implications for the positioning of brain-body circuit for UTIs treatment.